DECENTRALIZATION TO ACHIEVE REGIONAL INDEPENDENCE WITH COMPETITIVE ADVANTAGE AS A MODERATION - Agustina Br Surbakti; Lakharis Inuzula; Zulkarnaini; Kheriah; Yusmika Indah; Salman (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the influence of decentralization, competitive advantage on the level of regional independence in the Lhokseumawe City government, and measure the magnitude of the interaction between decentralization and competitive advantage on the level of regional independence in the Lhokseumawe City government. Decentralization has aspects of strong and quality resource mechanisms, to management strategies including being superior in competing. Local governments must have the right method to be able to compete, so as to fulfill aspects of healthy and sustainable competitive advantage. Referring to competitive advantage, local governments must determine the right strategy, appropriate and guarantee local governments to appear "different" from other regions. Through this, the government will be able to guarantee the sustainability and welfare of the community in the long term. This study uses Moderated Regression Analysis (MRA) with data processing using SEM-PLS. Determination of the sample using Purposive Sampling of all apparatuses in the Lhokseumawe City Regional Work Unit with the number of selected samples being 122 apparatuses. The results of the study found that decentralization and competitive advantage had a significant effect on the level of regional independence. While competitive advantage has succeeded in becoming a quasi-moderation function, which means that the better the decentralization supported by competitive advantage, the higher the level of regional independence. Thus, the value of Regional Original Income (PAD) will be higher as an indicator of the expected level of independence.